Population pharmacokinetics for danofloxacin in the intestinal contents of healthy and infected chickens. Issue 5 (19th August 2019) - Tian, Erjie; Chen, Chunli; Hu, Wanjun; Miao, Yusong; Muhammad, Ishfaq; Zhang, Qiaomei; Liu, Yuhao; Xu, Liang; Bao, Jiaxin; Ding, Liangjun; Li, Jichang
Abstract: Avian pathogenic Escherichia coli could cause localized and systemic infection in the poultry, and danofloxacin is usually used to treat avian colibacillosis through oral administration. To promote prudent use of danofloxacin and reduce the emergence of drug‐resistant E. coli strains, it is necessary to understand the population pharmacokinetics (PopPK) of danofloxacin in chicken intestines. In this study, reversed‐phase high performance liquid chromatography (HPLC) with fluorescence detection was used to detect the concentrations of danofloxacin in the contents of duodenum, jejunum, and ileum of the healthy and infected chickens after single oral administration (5 mg/kg body weight). Then, the PopPK of danofloxacin in intestines were analyzed using NONMEM software. As a result, a two‐compartment PK model best described the time‐concentration profile of duodenal, jejunal, and ileal contents. Interestingly, absorption rate ( K a ), distribution volume ( V ), and clearance (CL) for danofloxacin from duodenal, jejunal to ileal contents were sequentially decreased in the healthy chickens. However, the trend of K a, V, and CL of danofloxacin was changed dramatically in the intestine of infected chickens. K a and V of danofloxacin in the jejunum were higher than in the ileum and duodenum. Compared with healthy chickens, K a and V of danofloxacin in the duodenum decreased significantly, while increased in jejunum, respectively. It has been noted that K a decreased and V increased in the ileum of infected chickens. Besides, CL in the duodenum, jejunum, and ileum of infected chickens was, respectively, lower than those of healthy chickens. Interestingly, the relative bioavailability ( F ) of danofloxacin in the ileum was relatively higher in both healthy and infected chickens. In addition, F in the duodenal, jejunal, and ileal contents of infected chickens was respectively higher than healthy chickens. In summary, the PopPK for danofloxacin in infected chicken intestines was quite different from healthy chickens. The absorption, distribution, and clearance of danofloxacin in healthy chickens decreased from duodenum to jejunum and to ileum. Moreover, the pharmacokinetic characteristics in the intestine of infected chickens changed significantly, and the pharmacokinetic characteristics in the ileum can be used as a representative of all intestinal segments.